Comparative long-term outcomes of pembrolizumab plus chemotherapy versus pembrolizumab monotherapy as first-line therapy for metastatic non-small-cell lung cancer: a systematic review and network meta-analysis - Huang, Shibo; Huang, Zhilong; Huang, Xiaolong; Luo, Raoshan; Liang, Weiming; Qin, Tian (Frontiers in Immunology, 2024)
Introduction This systematic review and network meta-analysis(NMA) was designed to compare the long-term outcomes of pembrolizumab monotherapy and pembrolizumab plus chemotherapy as first-line therapy for metastatic non-small-cell lung cancer(NSCLC). Materials and Methods Four databases(Medline, Embase, Web of Science and CENTRAL were searched published from establishment of database to August 17, 2023, for articles studying pembrolizumab monotherapy or pembrolizumab plus chemotherapy for non-small cell lung cancer (NSCLC). Network meta-analyses of progression-free survival(PFS), overall survival(OS), objective response rate(ORR), treatment-related adverse events(trAEs) and immune-related adverse events(irAEs) were performed. Results A total of five studies were considered for NMA. This NMA includes a cohort of 2878 patients diagnosed with advanced NSCLC. Among them, 791 patients received pembrolizumab monotherapy, 1337 patients received chemotherapy, and 748 patients received pembrolizumab plus chemotherapy. The IPDformKM software was utilized to reconstruct Kaplan-Meier curves for OS and PFS, offering a lucid and intuitive depiction of oncological outcomes. For patients who have high levels of programmed death-ligand 1(PD-L1) expression (≥50%), pembrolizumab plus chemotherapy was more effective than using pembrolizumab alone as first-line therapy in terms of PFS (median survival time: 10.41 months versus 7.41 months, HR: 0.81, 95%CI 0.67 to 0.97, P=0.02) and ORR (RR:1.74, 95% CI: 1.25-2.43). Nevertheless, there was no statistically significant difference observed between the two groups in terms of OS (median survival time: 22.54 months versus 22.62 months, HR: 0.89, 95%CI 0.73 to 1.08, P=0.24). Conclusions The present network meta-analysis reported comparative long-term outcomes of pembrolizumab plus chemotherapy versus pembrolizumab monotherapy as first-line therapy for metastatic non-small-cell lung cancer. Pembrolizumab plus chemotherapy led to improved PFS and ORR in patients with advanced NSCLC who had a PD-L1 expression level of 50% or above. However, there was no noticeable benefit in terms of OS when pembrolizumab was paired with chemotherapy compared to utilizing pembrolizumab alone.